2013
DOI: 10.1111/fwb.12168
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic grazers reduce the establishment and growth of riparian plants along an environmental gradient

Abstract: Summary The establishment of riparian plants is determined by abiotic conditions and grazing, although it is usually presumed that the former are most important. We tested the impact of aquatic grazers on the survival and growth of establishing riparian plants and whether the impact of grazing interacts with abiotic conditions. We conducted an experiment across 10 Dutch wetlands, covering a large range of water depth and nutrient availability. We introduced 1‐year‐old plants of an emergent (common reed, Phra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
1
10
0
1
Order By: Relevance
“…The main herbivores on submerged aquatic vascular plants are generalists such as waterfowl, crayfish and snails (Lodge et al 1998;Parker & Hay 2005;Wood et al 2016) and they strongly regulate plant abundance and ecosystem processes (Lodge et al 1998;Veen et al 2013;van der Wal et al 2013;Bakker et al 2016). Unsurprisingly therefore, consumers provide most biotic resistance to plant invasions in aquatic ecosystems (Kimbro, Cheng & Grosholz 2013;Alofs & Jackson 2014).…”
Section: S T U D Y S Y S T E Mmentioning
confidence: 99%
“…The main herbivores on submerged aquatic vascular plants are generalists such as waterfowl, crayfish and snails (Lodge et al 1998;Parker & Hay 2005;Wood et al 2016) and they strongly regulate plant abundance and ecosystem processes (Lodge et al 1998;Veen et al 2013;van der Wal et al 2013;Bakker et al 2016). Unsurprisingly therefore, consumers provide most biotic resistance to plant invasions in aquatic ecosystems (Kimbro, Cheng & Grosholz 2013;Alofs & Jackson 2014).…”
Section: S T U D Y S Y S T E Mmentioning
confidence: 99%
“…Further, the high variability of natural seedling numbers between 2013 and 2014 suggest that additional external factors, such as wave action or herbivory, may decouple the relationship between stranding and diversity (Sarneel & Soons ; Veen et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands, a study of eutrophic peaty lakes found that grazing by waterfowl greatly reduced macrophyte biomass (Haterd and Heerdt 2007); and in a wetlands study (Veen et al 2013), biomass of S. aloides decreased from 24.8 to 9.3 g (60%) in plots which were not enclosed, the damage to leaves and stems attributed primarily to the aquatic birds present in the studied plots, including ducks, swans and coots.…”
Section: Birds and Other Vertebratesmentioning
confidence: 92%
“…Although the muskrat, Ondatra zibethicus L., and livestock, such as cattle and sheep, are believed to occasionally graze on S. aloides, the effects of such grazing are difficult to measure because of the presence of grazing aquatic birds (Veen et al 2013). …”
Section: Mammals Including Both Domestic and Wild Animalsmentioning
confidence: 99%